Dynamic Acclimation to High Light in Arabidopsis thaliana Involves Widespread Reengineering of the Leaf Proteome - Miller, Matthew A. E.; O’Cualain, Ronan; Selley, Julian; Knight, David; Karim, Mohd F.; Hubbard, Simon J.; Johnson, Giles N. (Frontiers in Plant Science, 2017)
Leaves of Arabidopsis thaliana transferred from low to high light increase their capacity for photosynthesis, a process of dynamic acclimation. A mutant, gpt2, lacking a chloroplast glucose-6-phosphate/phosphate translocator, is deficient in its ability to acclimate to increased light. Here, we have used a label-free proteomics approach, to perform relative quantitation of 1993 proteins from Arabidopsis wild type and gpt2 leaves exposed to increased light. Acclimation to light is shown to involve increases in electron transport and carbon metabolism but no change in the abundance of photosynthetic reaction centres. The gpt2 mutant shows a similar increase in total protein content to wild type but differences in the extent of change of certain proteins, including in the relative abundance of the cytochrome b6f complex and plastocyanin, the thylakoid ATPase and selected Benson-Calvin cycle enzymes. Changes in leaf metabolite content as plants acclimate can be explained by changes in the abundance of enzymes involved in metabolism, which were reduced in gpt2 in some cases. Plants of gpt2 invest more in stress-related proteins, suggesting that their reduced ability to acclimate photosynthetic capacity results in increased stress.